Pore-Mouth Structure of Highly Agglomerated Detonation Nanodiamonds - Elda Zoraida Piña-Salazar (MDPI AG, 2021)
Detonation nanodiamond aggregates contain water that is removed by thermal treatments in vacuo, leaving available pores for the adsorption of target molecules. A hard hydrogel of detonation nanodiamonds was thermally treated at 423 K for 2 h, 10 h, and 52 h in vacuo to determine the intensive water adsorption sites and clarify the hygroscopic nature of nanodiamonds. Nanodiamond aggregates heated for long periods in vacuo agglomerate due to the removal of structural water molecules through the shrinkage and/or collapse of the pores. The agglomerated nanodiamond structure that results from long heating periods decreases the nitrogen adsorption but increases the water adsorption by 40%. Nanodiamonds heated for long times possess ultramicropores <0.4 nm in diameter in which only water molecules can be adsorbed, and the characteristic mouth-shaped mesopores adsorb 60% more water than nitrogen. The pore mouth controls the adsorption in the mesopores. Long-term dehydration partially distorts the pore mouth, decreasing the nitrogen adsorption. Furthermore, the nitrogen adsorbed at the pore mouth suppresses additional nitrogen adsorption. Consequently, the mesopores are not fully accessible to nitrogen molecules because the pore entrances are blocked by polar groups. Thus, mildly oxidized detonation nanodiamond particles can show a unique molecular sieving behavior.